Character Education in Business Schools: Pedagogical Strategies - Hill, Alexander (Teaching business ethics, 1999)
This manuscript commences by articulating the need for character education in business schools. It proceeds to discuss several pedagogical strategies that develop virtue in students. The concept of character education, derived from a variety of cultures -- including the ancient Greeks -- includes cognitive, affective and behavioral realms. As such, it seeks not only to develop students' intellectual capabilities but to make them people of virtue as well. Particular pedagogical strategies addressed in the article include teaching virtues via narrative, mentor relationships, collaborative learning, service-learning and self-reflection. Programs of a number of universities are cited as examples.